SELECTED RENEWABLE ENERGY LEGAL ISSUES IN THE CONTEXT OF LOGISTICS MANAGEMENT - Aneta Suchoń (Journal of Agribusiness and Rural Development, 2015)
The purpose of the paper is, fi rstly, to present renewable energy sources in Poland compared with other EU countries and, secondly, to evaluate legal regulations relating to the implementation of renewable energy projects and to operation in the context of logistics management. The article also presents the defi nition and statistical data on renewable energy. Then, it focuses on legal aspects of the building process of wind farms and biogas plants. It also points out the process of organising the project, including ensuring a legal title to lands and obtaining, apart from the building permit, some other decisions. Next, the paper raises selected issues of fi nancing the projects and of a contract engineer. Finally, it refers to the stage of operating the biogas plants and to the obligations relating to the agricultural biogas.